Fabrication of Cobalt-Nickel-Zinc Ternary Oxide Nanosheet and Applications for Supercapacitor Electrode - Wu, Chun; Chen, Lei; Lou, Xuechun; Ding, Mei; Jia, Chuankun (Frontiers in Chemistry, 2018)
Mesoporous Cobalt-Nickel-Zinc ternary oxide (CNZO) nanosheets grown on the nickel foam are prepared by a simple hydrothermal treatment and subsequent calcination process. The physical characterizations show that the as-obtained CNZO nanosheets possess the mesoporous structure and a high specific surface of 75.4 m2 g-1 has been achieved. When directly applied for the binder-free supercapacitor electrode for the first time, the nickel foam supported mesoporous CNZO nanosheet electrode exhibits an ultrahigh specific capacity about 1172.2 C g-1 at 1 A g-1. More significantly, an asymmetric supercapacitor based on the as-obtained CNZO positive electrode and an activated carbon negative electrode shows a high energy density of 84.2 Wh kg-1 at a power density of 374.8 W kg-1, with excellent cycle stability (keeps 78.8% capacitance retention and 100% coulombic efficiency after 2500 cycles). The excellent supercapacitive properties suggest that the nickel foam supported CNZO nanosheet electrodes are promising for application as high-performance supercapacitor.